Managers’ perspectives on restaurant food waste separation intention: The roles of institutional pressures and internal forces - Ng, P.Y.; Sia, Joseph (ELSEVIER SCI LTD, 2023)
The hospitality industry, particularly restaurants, generates a large amount of food waste daily. This study draws upon institutional theory using the lens of isomorphic pressures and two internal factors, corporate social responsibility (CSR) and restaurant size, to investigate what drives food waste separation intention in the restaurant sector of a developing economy. Data collected from 395 restaurant managers show that normative, coercive, and mimetic pressures positively impact intention; isomorphic pressures are mediated by CSR to achieve higher intention; and the crucial interaction between restaurant size and CSR significantly strengthens food waste separation intention. The study contributes to institutional theory by offering a novel integrated model to explain the respective mediating and moderating roles that CSR and restaurant size play between institutional pressures and behavioral intention in food waste management.